2018
DOI: 10.3390/nano8060413
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Sensitive Resistive Pressure Sensor Based on a Carbon Nanotube-Liquid Crystal-PDMS Composite

Abstract: Resistive pressure sensors generally employ microstructures such as pores and pyramids in the active layer or on the electrodes to reduce the Young’s modulus and improve the sensitivity. However, such pressure sensors always exhibit complex fabrication process and have difficulties in controlling the uniformity of microstructures. In this paper, we demonstrated a highly sensitive resistive pressure sensor based on a composite comprising of low-polarity liquid crystal (LPLC), multi-walled carbon nanotube (MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…The various approaches in fabricating pressure sensors include resistive types [7,21,39,70,95,104,127,136,208,296,[413][414][415][416][417][418][419][420][421][422][423], capacitive types [25,71,146,303,310,321,352,[424][425][426][427], field-effect transistors [9][10][11]193,428], and the piezocapacitive and piezoelectric properties of materials [214,[429][430][431]. Pressure sensors' most important parameters are sensitivity, detection range and response time.…”
Section: Pressure Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The various approaches in fabricating pressure sensors include resistive types [7,21,39,70,95,104,127,136,208,296,[413][414][415][416][417][418][419][420][421][422][423], capacitive types [25,71,146,303,310,321,352,[424][425][426][427], field-effect transistors [9][10][11]193,428], and the piezocapacitive and piezoelectric properties of materials [214,[429][430][431]. Pressure sensors' most important parameters are sensitivity, detection range and response time.…”
Section: Pressure Sensorsmentioning
confidence: 99%
“…Recent developments in fabricating resistive pressure sensors have included the use of CNTs [417,419,420], AgNWs [95], ZnO [422], graphene [8,95,417,418] and conductive polymers [8,70,136].…”
Section: Resistive Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A surface plasmon resonance (SPR) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ] is formed when the incident electrons resonate with the vibration on the surface of metallic nanostructures, which has caused broad interest regarding novel applications [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Researchers have shown that plasmonic crystals [ 20 , 21 ] are essential for superlenses [ 22 , 23 ], negative refraction applications [ 24 , 25 ], and ultra-large nonlinearity devices [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have been utilized either polydimethylsiloxane (PDMS) or polyurethane (PU) as elastic matrices for highly sensitive, flexible pressure sensors, allowing tailoring of their shapes and structures [ 16 , 25 , 26 , 27 , 28 , 29 ]. However, elastic matrices, such as PDMS and PU, have the major limitation of poor processability (poor adhesion) originating from their low surface energies, making these polymers difficult to use in practical applications [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%